CONVERSATIONAL IMPLICATURE BETWEEN AN ENGLISH TEACHER AND STUDENTS - Reza, Muhammad; Suhartono, Luwandi; Rezeki, Yanti Sri (Sanata Dharma University, Yogyakarta, 2025)
This study analyzed the conversational implicatures in the conversation between the English teacher and the students during an English class session in one of the classrooms at SMP Negeri 9 Pontianak. The purposes of this study were to identify the types of conversational implicatures used by the English teacher and the students, and also to describe the implied meaning of the conversational implicatures used by the English teacher and the students during one English class session in the classroom. This study focused on analyzing the conversation using Paul Grice’s theory of conversational implicature. The results of this study demonstrated the usage of two different types of conversational implicature by both the teacher and the students: generalized and particularized. The analysis also demonstrated that the implied meanings derived from these conversational implicatures conveyed a variety of communicative purposes beyond the literal meaning of the words spoken. These included informing, requesting, ordering, confirming, and expressing ignorance.